2015
DOI: 10.1038/nm.3929
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging and tracking of host–microbiota interactions via metabolic labeling of gut anaerobic bacteria

Abstract: The intestine is densely populated by anaerobic commensal bacteria. These microorganisms shape immune system development, but our understanding of host–commensal interactions is hampered by a lack of tools for studying the anaerobic intestinal environment. We applied metabolic oligosaccharide engineering and bioorthogonal click-chemistry to label various commensal anaerobes, including Bacteroides fragilis, a common and immunologically important commensal. We studied the dissemination of B. fragilis following a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
208
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(211 citation statements)
references
References 36 publications
3
208
0
Order By: Relevance
“…In contrast, Western blot and flow cytometry analyses revealed that the azidosugar peracetylated N -azidoacetylgalactosamine (Ac 4 GalNAz), 43 an analog of N -acetylgalactosamine, was robustly displayed in B. fragilis surface glycans (Figure 5B,C; Supplementary Figure 4B); this result is consistent with a recent demonstration by Kasper and co-workers that Ac 4 GalNAz is processed into polysaccharide A in B. fragilis . 44 These data indicate that, though it is possible to incorporate azides into B. fragilis surface glycans, such incorporation is negligible with the rare bacterial monosaccharide analogs reported here. Thus, narrow range antibiotics based on differential incorporation of azides onto the surface of pathogenic but not symbiotic bacteria may be possible.…”
Section: Resultsmentioning
confidence: 59%
“…In contrast, Western blot and flow cytometry analyses revealed that the azidosugar peracetylated N -azidoacetylgalactosamine (Ac 4 GalNAz), 43 an analog of N -acetylgalactosamine, was robustly displayed in B. fragilis surface glycans (Figure 5B,C; Supplementary Figure 4B); this result is consistent with a recent demonstration by Kasper and co-workers that Ac 4 GalNAz is processed into polysaccharide A in B. fragilis . 44 These data indicate that, though it is possible to incorporate azides into B. fragilis surface glycans, such incorporation is negligible with the rare bacterial monosaccharide analogs reported here. Thus, narrow range antibiotics based on differential incorporation of azides onto the surface of pathogenic but not symbiotic bacteria may be possible.…”
Section: Resultsmentioning
confidence: 59%
“…Our platform for rapid modification of Bacteroides with strong and predictable expression adds to an emerging palette of tools (Earle et al, 2015; Geva-Zatorsky et al, 2015; Goodman et al, 2009; Koropatkin et al, 2008; Mimee et al, 2015) that can synergize to add new dimensions to our understanding of gut ecology. At one extreme, our data reveals new facets of Bacteroides promoter architecture providing an example of how our high throughput strain generation can yield basic molecular insight (Figure 4A).…”
Section: Discussionmentioning
confidence: 99%
“…Although much remains to be understood about microbial spatial distribution and the factors influencing microbial community organization, this imaging and analysis approach provides a new way to investigate host–microbiota interactions. The second study 32 used (MOE) and (BCC) in combination with whole-body imaging to label and track bacteria in vivo . Combining these techniques enabled researchers to track the distribution of a symbiotic bacterium along the intestinal tract, its ability to compete with other species and its interaction with host cells.…”
Section: Studying the Microbiomementioning
confidence: 99%